Purmorphamine Attenuates Neuro-Inflammation and Synaptic Impairments After Hypoxic-Ischemic Injury in Neonatal Mice via Shh Signaling - Liu, Dexiang; Bai, Xuemei; Ma, Weiwei; Xin, Danqing; Chu, Xili; Yuan, Hongtao; Qiu, Jie; Ke, HongFei; Yin, Sen; Chen, Wenqiang; Wang, Zhen (Frontiers in Pharmacology, 2020)
Purmorphamine (PUR), an agonist of the Smoothened receptor, has been shown to function as a neuroprotectant in acute experimental ischemic stroke. Its role in hypoxic-ischemic (HI) brain injury in neonatal mice remains unknown. Here we show that PUR attenuated acute brain injury, with a decrease in Bax/Bcl-2 ratio, inhibition of caspase-3 activation. These beneficial effects of PUR were associated with suppressed neuro-inflammation and oxidative stress. PUR exerted long-term protective effects upon tissue loss and improved neurobehavioral outcomes as determined at 14 and 28 days post-HI insult. Moreover, PUR increased synaptophysin and PSD95 expression in HI-treated mice and attenuated synaptic loss. PUR up-regulated the expression of Shh pathway mediators, while suppression of the Shh signaling pathway with cyclopamine reversed these beneficial effects of PUR on HI insult. Our study suggests a therapeutic potential for short-term PUR administration in HI-induced injury as a result of its capacity to exert multiple protective actions upon acute brain injury, long-term memory deficits and impaired synapses. Moreover, we provide evidence indicating that one of the mechanisms underlying these beneficial effects of PUR involves activation of the Shh signaling pathway.